Management of Incidental Finding of Triorchidism Diagnosed During Routine Hernia Repair - Balawender K; Wiatr T; Wawrzyniak A; Orkisz S (Research and Reports in Urology, 2021)
Krzysztof Balawender,1,2 Tomasz Wiatr,3 Agata Wawrzyniak,2 Stanisław Orkisz2 1Department of Urology and Urological Oncology, Municipal Hospital in Rzeszow, Rzeszow, Poland; 2Morphological Sciences Department of Human Anatomy, Institute of Medical Sciences, Medical College of Rzeszow University, Rzeszow, Poland; 3Jagiellonian University Medical College, Department of Urology, Cracow, PolandCorrespondence: Krzysztof BalawenderDepartment of Urology and Urological Oncology, Municipal Hospital in Rzeszow, Rycerska 4, Rzeszow, 35-241, PolandEmail balawender82@gmail.comAbstract: Polyorchidism is a rare congenital anomaly which refers to the presence of more than two intra- or extrascrotal testicles. Triorchidism, the presence of one extra testicle is the most common type. This report describes the case of a 29-year-old male who was found to have a right supernumerary undescended testis encountered incidentally during hernia repair. With this in mind, the current knowledge of management of supernumerary testis was analysed, including potential scenarios, to delineate what a urologist should do when a supernumerary testis is found during routine surgical procedures such as orchidopexy or hernia repair.Keywords: triorchidism, polyorchidism, supernumerary testis, orchidectomy, orchidopexy